Diseño editorial como herramienta a la socialización de indicadores críticos de suicidio en jóvenes de 20 a 25 años en la Universidad Técnica de Ambato - Zurita Gallo, Emma Juliana (2025)
The Technical University of Ambato (UTA) is a higher education institution dedicated to training professionals with solid academic and practical preparation, through the development of undergraduate and postgraduate programs in various areas of knowledge. This thesis explores editorial design as a tool for socializing critical suicide indicators among young people aged 20 to 25 at UTA, a population vulnerable to this phenomenon. The research responds to the growing concern about suicides among university students and the need to raise awareness of risk factors. The methodology combines qualitative and quantitative approaches, through interviews with mental health experts and surveys of students and staff at UTA. Additionally, the effectiveness of existing editorial materials was analyzed. The results reveal a low level of knowledge about suicide indicators among students. The proposal is to design interactive editorial materials, such as posters, brochures, and digital content, that provide clear information on the risks and warning signs of suicide. These materials will be available in high-traffic areas of the university to raise awareness within the community and promote self-care. In conclusion, editorial design is essential for increasing awareness of suicide among university youth and can be an effective tool for reducing stigma and promoting prevention at UTA